(untitled) - Tōji, Kamata (Tokyo, 2017)
This English translation of a book originally written in Japanese by one of the country's most knowledgeable, penetrating, and eclectic scholars of Japanese religion and spirituality presents an engaging overview of the country's religious legacy, as well as offering insights into how religion can become a force for peaceful coexistence, rather than violent extremism.
Keywords: Buddhism and psychoanalysis.,Buddhism,Phật giáo; Relations,Shinto.,Thần đạo.,Quan hệ